Voluntary disclosures and insider transactions - Noe, Christopher F. (Journal of Accounting and Economics, 1999)
This paper investigates the association between voluntary disclosures and insider transactions (i.e., transactions by managers in their own firms’ shares). The findings suggest that managers do not make insider transactions to profit from news about their own firms just before it becomes publicly available. However, managers appear to employ other strategies for exploiting private information when making insider transactions. Managers cluster insider transactions after voluntary disclosures when doing so results in more favorable stock prices for them. Also, managers take advantage of knowledge about their own firms’ long-term prospects while utilizing voluntary disclosures to shield themselves against profiteering allegations.